Amplifying the value of the third space to support strategic curriculum change - Annie Yonkers; Hilary Wason (Journal of Learning Development in Higher Education)
This case study presents how we at Kingston University have expanded our collaborative ‘third space’ to support the delivery of an ambitious blueprint of skills development in the curriculum. In 2022, Kingston embarked on an ambitious journey to roll out a progressive model of education through a new strategic initiative embedding personal and professional development for all undergraduate students as a core element of their course. This strategy was developed as a threefold response to an evolving education landscape in the UK. First, drawing on Kingston’s ‘Future Skills’ research on skills and the economy to influence at a sector level (Kingston University, 2023). Second, as a response to the updated OfS conditions of registration (specifically the B3 conditions). Third, to enhance our existing commitment to equitable and inclusive support for students.